Role of biofuels in energy transition, green economy and carbon neutrality - Nida, Khan; Sudhakar, K.; R., Mamat (MDPI, 2021)
Modern civilization is heavily reliant on petroleum-based fuels to meet the energy demand of the transportation sector. However, burning fossil fuels in engines emits greenhouse gas emissions that harm the environment. Biofuels are commonly regarded as an alternative for sustainable transportation and economic development. Algal-based fuels, solar fuels, e-fuels, and CO2-to-fuels are marketed as next-generation sources that address the shortcomings of first-generation and second-generation biofuels. This article investigates the benefits, limitations, and trends in different generations of biofuels through a review of the literature. The study also addresses the newer generation of biofuels highlighting the social, economic, and environmental aspects, providing the reader with information on long-term sustainability. The use of nanoparticles in the commercialization of biofuel is also highlighted. Finally, the paper discusses the recent advancements that potentially enable a sustainable energy transition, green economy, and carbon neutrality in the biofuel sector.